Forecasting Stock Prices Using LSTM and ARIMA Models - Aydın, Yıldız; Varol, Gizem; Gökdeniz, Eyyüb Ensari; Manus, Hakan (Fırat University, 2024)
The stock market traded on Borsa Istanbul is one of the most popular investment instruments today. In fact, Turkey is one of the top five countries with the highest number of transactions per capita. The development of technology has not only made it easier for investors to turn to such investment instruments but also facilitated the analysis methods. This study aims to compare the LSTM and ARIMA models, which are among the analysis methods used, to see which one provides better performance. Unlike other studies, this study was conducted using data from the years 2020-2024 and took sectoral differences into consideration. The results showed that LSTM is more effective in capturing complex and long-term dependencies. This will help investors make more informed decisions when choosing a model.

Borsa İstanbul’da işlem gören hisse senedi piyasası, günümüzde en çok rağbet gören yatırım araçlarından biridir. Öyle ki nüfusa göre en çok işlem gerçekleştirilen ilk beş ülkeden biri Türkiye’dir. Teknolojinin gelişimi, yatırımcıların bu gibi yatırım araçlarına yönelmesini kolaylaştırmasının yanı sıra analiz yöntemlerini de kolaylaştırmıştır. Bu çalışma, kullanılan analiz yöntemlerinden olan LSTM ve ARIMA modellerini karşılaştırıp, hangisinin daha iyi performans sağladığını görmek için yapılmıştır. Çalışmada diğer çalışmalardan farklı olarak 2020-2024 yılları arasındaki verilerle gerçekleştirilmiş ve sektörel farklılıklar göz önünde bulundurularak işlem yapılmıştır. Sonuçlar, LSTM’nin karmaşık ve uzun vadeli bağımlılıkları yakalamada daha etkili olduğunu göstermiştir. Bu, yatırımcıların model seçimini yaparken daha bilinçli kararlar almasına yardımcı olacaktır.
Hisse Senedi Fiyatlarının LSTM ve ARIMA Modelleri Kullanılarak Tahmin Edilmesi
Keywords: Deep Learning; Derin Öğrenme